The Role of Islamic Microfinance Institutions in Poverty Reduction: A Study of Scopus Indexed Journal Literature - Pupun Saepul Rohman; Nisful Laila; Atina Shofawati (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to reveal the development of research on the theme of Islamic microfinance institutions from reputable international journals. This study uses a qualitative approach, namely literature review. The literature search went through a series of stages to ensure that only papers sourced from reputable journals were featured in this study. The results of the study found that there were 181 papers with the theme of Islamic microfinance institutions from international journals indexed by Scopus. The development of research related to Islamic microfinance has increased, especially in the last three years (2019, 2020, 2021). The implication of this research is that this study proves in the literature the important role of Islamic microfinance institutions in alleviating poverty. This is a valuable input for related parties, especially the government, to pay more attention to the infrastructure required by Islamic microfinance institutions.